2001
DOI: 10.1002/1096-9861(20010129)430:1<131::aid-cne1019>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the timing of acute blood‐brain barrier breakdown to rabbit immunoglobulin G in the cerebellum and spinal cord of mice with experimental autoimmune encephalomyelitis

Abstract: Experimental autoimmune encephalomyelitis (EAE) is an animal model for human multiple sclerosis (MS). Similar to MS patients, EAE animals can exhibit chronic or relapsing, remitting paralysis; leukocyte infiltration of the central nervous system (CNS); and breakdown of the blood-brain barrier (BBB), allowing access to serum components. EAE pathology in rodents is generally thought to progress from the spinal cord to the more rostral brain. This common notion is based on numerous reports on the severity and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The neurogenically controlled changes related to cerebrovascular tone, particularly at the level of the neurovascular unit (26,27), are consistent with an increasing body of evidence in both EAE (45,46) and MS (47,48) that subtle, progressive alterations in BBB integrity precede the formation of inflammatory lesions. Hrh3 is linked to Eae8.…”
Section: Discussionsupporting
confidence: 77%
“…The neurogenically controlled changes related to cerebrovascular tone, particularly at the level of the neurovascular unit (26,27), are consistent with an increasing body of evidence in both EAE (45,46) and MS (47,48) that subtle, progressive alterations in BBB integrity precede the formation of inflammatory lesions. Hrh3 is linked to Eae8.…”
Section: Discussionsupporting
confidence: 77%
“…Disruption of the blood-brain barrier (BBB) at the cerebellum occurs early in disease in Lewis rats as visualized using ultra small particles of iron oxide (USPIO) in MRI (Floris et al, 2004; Rausch et al, 2003). The same has been shown in SJL/J mice with proteolipid protein (PLP) peptide 139–151-induced EAE, where cerebellar BBB breakdown was demonstrated to occur prior to disruption of the BBB in the spinal cord and prior to the development of clinical symptoms (Tonra, 2002; Tonra et al, 2001). Interestingly, this work demonstrated that the rabbit immunoglobulins used to evaluate BBB breakdown accumulated around Purkinje cells.…”
Section: Discussionmentioning
confidence: 56%
“…For example, adult neurogenesis has been demonstrated along perivascular sites within the subventricular and subgranular zones of the CNS following ischemic cerebral infarct (40). Alternatively, expansions in Virchow‐Robin perivascular space have recently been demonstrated during heightened disease activity in MS (41) and these spaces may expand similarly in EAE at the peak of disability when blood‐brain barrier lesions within the mouse brain are at their peak, particularly in somatosensory regions of cortex (42, 43). Therefore, immune cell foci within enlarged perivascular spaces may release factors that compete with chemoattractive signals for NPCs that are released along fiber tracts containing demyelinated axons originating from relatively dispersed cell bodies.…”
Section: Discussionmentioning
confidence: 99%